2018
DOI: 10.1073/pnas.1719033115
|View full text |Cite
|
Sign up to set email alerts
|

Serine metabolism in the brain regulates starvation-induced sleep suppression in Drosophila melanogaster

Abstract: SignificanceForaging and sleep are two conflicting behaviors in starved animals; however, it remains elusive how metabolic status governs sleep drive. In this study, we show that a biosynthetic pathway for the amino acid serine is transcriptionally up-regulated by starvation in adult fly brains. The behavioral response to genetic manipulation of key enzymes involved in serine metabolism supports the sleep-suppressing effect of serine in response to starvation. In a society where daily diet is becoming increasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 41 publications
0
29
1
Order By: Relevance
“…While many studies have examined the interactions between sleep and feeding, these have typically compared fed and starved animals without examining the effects of specific dietary components on sleep regulation [11,[69][70][71]. In Drosophila, feeding of a sugar only diet is sufficient for normal sleep duration [11], and evidence suggests that activation of sweet taste-receptors alone is sufficient to promote sleep [68,72].…”
Section: Plos Geneticsmentioning
confidence: 99%
See 1 more Smart Citation
“…While many studies have examined the interactions between sleep and feeding, these have typically compared fed and starved animals without examining the effects of specific dietary components on sleep regulation [11,[69][70][71]. In Drosophila, feeding of a sugar only diet is sufficient for normal sleep duration [11], and evidence suggests that activation of sweet taste-receptors alone is sufficient to promote sleep [68,72].…”
Section: Plos Geneticsmentioning
confidence: 99%
“…Numerous factors have been identified as essential regulators of starvation-induced sleep suppression. For example, we have found that flies mutant for the mRNA/DNA binding protein translin, the neuropeptide Leucokinin, and Astray, a regulator of serine biosynthesis, fail to suppress sleep when starved [39,69,70]. Further, activation of orexigenic Neuropeptide F-expressing neurons or the sweet-sensing Gr64f-expressing neurons suppress sleep, suggesting that activation of feeding circuits may directly inhibit sleep [72,81].…”
Section: Plos Geneticsmentioning
confidence: 99%
“…While many studies have examined the interactions between sleep and feeding, these have typically compared fed and starved animals without examining the effects of specific dietary components on sleep regulation [11,36,66,67]. In Drosophila , feeding of a sugar only diet is sufficient for normal sleep duration [68], and evidence suggests that activation of sweet taste-receptors alone is sufficient to promote sleep [65,69].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous factors have been identified as essential regulators of starvation-induced sleep suppression. For example, we have found that flies mutant for the mRNA/DNA binding protein translin , the neuropeptide Leucokinin , and Astray, a regulator of serine biosynthesis, fail to suppress sleep when starved [38,66,67]. Further, activation of orexigenic Neuropeptide F -expressing neurons or the sweet-sensing Gr64f -expressing neurons suppress sleep, suggesting that activation of feeding circuits may directly inhibit sleep [69,77].…”
Section: Discussionmentioning
confidence: 99%
“…This phenotype occurs across diverse Drosophila melanogaster laboratory strains and outbred lines (Brown et al, 2018; Masek et al, 2014), suggesting it is not an artifact of laboratory breeding. While previous work has shown that flies fed a diet of sugar alone sleep more than starved flies (Hasegawa et al, 2017; Keene et al, 2010; Sonn et al, 2018; B. Stahl, Slocumb, Chaitin, DiAngelo, & Keene, 2017), and that high calorie diets disrupt sleep (Catterson et al, 2010; Yamazaki et al, 2012), the contributions of different dietary macronutrients to sleep regulation has not been studied systematically.…”
Section: Discussionmentioning
confidence: 99%